Sugar-protein connectivity impacts on the immunogenicity of site-selective salmonella O-antigen glycoconjugate vaccines - Stefanetti, G; Hu, Q; Usera, A; Robinson, Z; Allan, M; Singh, A; Imase, H; Cobb, J; Zhai, H; Quinn, D; Lei, M; Saul, A; et al. (Wiley, 2010)
A series of glycoconjugates with defined connectivity were synthesized to investigate the impact of coupling Salmonella typhimurium O-antigen to different amino acids of CRM197 protein carrier. In particular, two novel methods for site-selective glycan conjugation were developed to obtain conjugates with single attachment site on the protein, based on chemical modification of a disulfide bond and pH-controlled transglutaminase-catalyzed modification of lysine, respectively. Importantly, conjugation at the C186-201 bond resulted in significantly higher anti O-antigen bactericidal antibody titers than coupling to K37/39, and in comparable titers to conjugates bearing a larger number of saccharides. This study demonstrates that the conjugation site plays a role in determining the immunogenicity in mice and one single attachment point may be sufficient to induce high levels of bactericidal antibodies.